SIRT1 mediates hypoxic postconditioning- and resveratrol-induced protection against functional connectivity deficits after subarachnoid hemorrhage. Issue 7 (July 2022) - Clarke, Julian V; Brier, Lindsey M; Rahn, Rachel M; Diwan, Deepti; Yuan, Jane Y; Bice, Annie R; Imai, Shin-ichiro; Vellimana, Ananth K; Culver, Joseph P; Zipfel, Gregory J
Functional connectivity (FC) is a sensitive metric that provides a readout of whole cortex coordinate neural activity in a mouse model. We examine the impact of experimental SAH modeled through endovascular perforation, and the effectiveness of subsequent treatment on FC, through three key questions: 1) Does the endovascular perforation model of SAH induce deficits in FC; 2) Does exposure to hypoxic conditioning provide protection against these FC deficits and, if so, is this neurovascular protection SIRT1-mediated; and 3) does treatment with the SIRT1 activator resveratrol alone provide protection against these FC deficits? Cranial windows were adhered on skull-intact mice that were then subjected to either sham or SAH surgery and either left untreated or treated with hypoxic post-conditioning (with or without EX527) or resveratrol for 3 days. Mice were imaged 3 days post-SAH/sham surgery, temporally aligned with the onset of major SAH sequela in mice. Here we show that the endovascular perforation model of SAH induces global and network-specific deficits in FC by day 3, corresponding with the time frame of DCI in mice. Hypoxic conditioning provides SIRT1-mediated protection against these network-specific FC deficits post-SAH, as does treatment with resveratrol. Conditioning-based strategies provide multifaceted neurovascular protection in experimental SAH.